Deriving The Psychometric Characteristics Of An Arabized Image Of The Social And Emotional Competencies Scale Of A Sample Of Secondary School Students In Najran Region - et. al., Dr.Ahmed Mohammed Bani Ismail , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study aimed to derive the psychometric characteristics (honesty and consistency) of Zych, Ruiz, Morales & Llorent, (2018) social and emotional competencies, and the sample of the study consisted of (544) students (244 males and 300 females) of secondary school students in Najran region. The results indicated the availability of indications of validity of the scale with indications (content honesty, validity of internal consistency). There were also acceptable indications of reliability for the scale, and the value of the alpha Cronbach for the scale as a whole was (0.91), and the value of the exploratory global validity of the scale reached (64.9). And the value of the Kimo test for compatibility between statement s was (0.87). The results indicated that there were statistically significant differences at the level of significance (0.05) on the scale of social and emotional competencies in favor of females. The study recommends codifying the scale among other categories.